The contribution of the International Rice Genebank to varietal improvement and crop productivity in Eastern India - Villanueva, Donald; Smale, Melinda; Jamora, Nelissa; Capilit, Grace Lee; Hamilton, Ruaraidh Sackville (Springer, 2020)
Using survey dataset collected from nearly 9000 farmers along with pedigree and evaluation data, this study measures the contribution of the International Rice Genebank (IRG) to varietal improvement and rice productivity of farmers in Eastern India. We empirically test the relationship of ancestry to productivity changes while controlling for the effects of other farm inputs and environmental factors. Estimated coefficients indicate that a 10% increase in the genetic contribution of IRG accessions to an improved rice variety is associated with a yield increase of 27%. Through pedigree analysis, we also confirm that 45 to 77% of the genetic composition of improved rice varieties is derived from the genes of IRG accessions. Peta, Dee Geo Woo Gen, and Fortuna are the three most popular progenitors with definite IRG contribution. High genealogical diversity likely results from the crossing of germplasm received from multiple countries of origin, which also confer multiple, functional trait combinations in a released variety. Further, our calculations reveal that the average coefficient of parentage of all pairwise combinations among the 10 most adopted rice varieties is 0.0973, indicating a high degree of latent genetic diversity. Findings demonstrate the valuable contribution of the genetic resources conserved and distributed by IRG to the development of improved rice varieties.